Characteristic, Emotional, and Behavioral Problems of Street Adolescent in Bandung OctoberâDecember 2012 - Nurfitriani, Annisa; Pandia, Veranita; Wiwaha, Guswan (Althea Medical Journal, 2015)
Background: Street adolescents were psychosocial problem that increased in number each year and was worsened by their low-moral subculture-value that could cause them more vulnerable in having emotional and behavioral problems. This study aims to describe the characteristics, emotional and behavioral problems of the street adolescent in Bandung.Methods: A descriptive study was carried out in OctoberâDecember 2012. From 22 shelters in Bandung, two shelters (RPA GANK and Pesantren Kolong Nurul Hayat) were selected and organized into 4 areas: Cihampelas, âSamsatâ, Laswi Street and Kiaracondong. A hundred-seven street adolescents aged 11 to 16 years were participated in this study. They were divided into small groups and filled in the sociodemographic questionnaire and the Indonesian version of standardized Strength and Difficulty Questionnaires (SDQ).Â  Only 100 questionnaires were filled in completely. Data were analyzed using frequency tabulation and bar chartResults: Sixty-five percent were boys, 53% were aged 11â13 years, and 53% were students, 76% related to more than one sibling, still lived with their families (81%), and had parents. Their parents had low educational background, had job, and implementedÂ  authoritative parenting pattern (41%). In becoming street adolescent, 63% were caused by their own motivation, 81% were children on street, and 55% had lived in the street more than 5 years. Approximately 27% of street adolescents were rated as abnormal on the total difficulty score. Â Conclusion: Street adolescent in Bandung still have emotional and behavioral problems, which mostly were boys, in the early adolescence stage, school student, had more than one sibling, permissive parenting pattern, and lived in the street for more than 5 years. [AMJ.2015;2(1):172â8]